Association between Streptococcus mutans levels and severity of caries in Ecuadorian schoolchildren aged 6 to 10 years. (International Journal of Medical and Surgical Sciences, 2018)
Dental caries is a multifactorial, infectious and communicable disease, and Streptococcus mutans is the key microorganism related to this pathology. The objective of this study was to evaluate the association between the levels of Streptococcus mutans and caries in schoolchildren. Descriptive, cross-sectional study conducted on 100 schoolchildren aged 6 to 10 years from the Unidad Educativa Checa Cuenca, Ecuador. ICDAS index and odontogram were used to measure the prevalence and severity of caries. For the identification and quantification of Streptococcus mutans , dental plaque samples were used for cultivation and biochemical tests (MicroScan). The results were analyzed statistically using absolute and relative frequencies, for bivariate analysis Chi-squared test and Fisher’s Test ( p